Impact of Participation in Young Smart Farmer Program on Smallholder Farmers' Income: A Propensity Score Matching Analysis - Poungchompu, Supaporn; Phuttachat, Porntip (Research on World Agricultural Economy, 2023)
The increase of elderly workers in the agricultural sector will decrease productivity using traditional agriculture production which causes the reduction of income. The Young Smart Farmer program is one of the solutions to solve the problem by developing new generation farmers' agricultural abilities replacing elderly farmers and creating incentives for the new generation to turn to agricultural occupation. Thus, this paper principally assessed the impact of the participation of young farmers in the YSF program on farm income and the determinants of the YSF program factor of young farmer's participation in the YSF program. The total number of samplings is 340 comprising 210 participants and 130 non-participants in the YSF program of the northeast area of Thailand. The data were analyzed using descriptive statistics and the propensity score matching approach to estimate the treatment effect of YSF participation on farm income among smallholder farmers. The results presented that the participants were younger with higher education, more experience and technology support, and had higher farm income compared to non-participants. The propensity scores matching results revealed a significant effect between farmer participation and farm income. The increase in farmers’ income from the participation of young smart farmers was estimated to be approximately 6758.59 $/year compared to non-participants of 3066.63 $/year. To encourage young people to participate more in the YSM program the government should provide more support that can stimulate the young farmers' farming economic activities to improve their quality of living and be fully satisfied with their livelihood. Also, the government should encourage a strong network within the group which consequently increases knowledge sharing, technology, and agricultural activities from the production process to marketing.